A Comparative Study of Coral Reef Cover Percentage Between Shallow and Deep Depths at Pramuka Island, Kepulauan Seribu - Ratna Clara Laksmitha; Muhammad Farhan Haidar Rahman; Try Feby Innocentia; Imam Fatoni; Ridha Rahman; Firsta Kusuma Yudha (Coastal and Ocean Journal (COJ), 2026)
Indonesia possesses one of the largest coral reef resources in the world, representing approximately 14% of global reef coverage, and these reefs are highly vulnerable to environmental changes and human activities, particularly in densely populated areas like Pramuka Island, Kepulauan Seribu. This research was conducted to evaluate reef conditions around Pramuka Island through an analysis of coral cover at two depth ranges, namely shallow waters (3–5 m) and deeper reef zones (8–10 m). Data collection utilized Line Intercept Transect (LIT) method at six stations, with three transect replications at each depth. The results showed a significant difference in live coral cover between shallow and deep depths (p=0.018). The highest cover and best condition (very good category) were found at Panggang Cultivation Area, linked to ongoing coral cultivation and transplantation activities. Reef conditions among the observation sites ranged from poor to very good, reflecting considerable spatial variation in coral ecosystem quality, with the dominant lifeform being Coral Massive (CM), indicating high resistance to local pressures.